?COMBINING ABILITY ANALYSIS IN MAIZE (ZEA MAYS L.) - Paul, K K; Debanth, S C (Biological Sciences - PJSIR, 1999)
Combining ability analysis was carried out in maize (Zea mays L.) in a 7x7 diallel, excluding reciprocals. Both the general CGCA)and specific combining ability (SCA) effects were significant for all the characters studied namely days topollen shedding,days tosilk,plantheight,earheightandbiomass weightperplant.Combining abilityanalysis indicated thatadditivegeneactionwasmoreimportantthan non-additivegeneactionandthebest general andspecific combiners were selected. Lines #7721 and #7785 showed significantly desirable GCA effects for days to pollen shedding and days to silk, S 2-9, for plant height, S 16-2,for ear height and#1018 and S16-2for biomass weight per plant. The number ofcrosses showingdesirable significantSCAeffects fordays topollen shedding,days to silk, plant height, ear height and biomass weightper plant were7,4, 6, 6 and 8 respectively.